The Effect Of Inflation, BI-7 Days Repo Rate, Credit Risk, and Liquidity Risk On The Financial Performance Of Conventional Commercial Banks With The 2017-2021 - Sabelia, Adinda; Sufina, Lediana (Jurnal Keuangan dan Perbankan, 2023)
This study aims to determine the effect of inflation, the BI-7 Days Repo Rate, Credit Risk, and Liquidity Risk on the Financial Performance of Conventional Commercial Banks with the 2017-2021 research period. Research objects using 39 conventional commercial banks listed on the Indonesia Stock Exchange using a purposive sampling method. Hypothesis testing using descriptive statistics with multiple linear regression analysis methods. The results indicate that Inflation has a positive effect on financial performance. The BI-7 Day Repo Rate has no effect on financial performance. Credit risk has a negative influence on financial performance. Liquidity risk has no effect on financial performance.